PARTISIPASI ANGGOTA P3A DALAM PEMELIHARAAN JARINGAN IRIGASI - Lili Afrylia Ibrahim; Welson M. Wangke; Melsje Y. Memah (AGRI-SOSIOEKONOMI, 2017)
This study aims to find out the participation of P3A (Farmers of water user Group) farmers in maintaining irrigation networks. The data used in this research is in the form of primary data and secondary data. Primary data obtained by direct observation at the location or interviews based on the questionnaires with members of the P3A Tara-tara Three Urban Village, Sub-district of West Tomohon, Tomohon City. While secondary data including articles related to research. The method of analysis used in this study is the random sampling method means that every member of the population has the same opportunities and opportunities to be selected as a sample. This study suggests that the participation of P3A members in the maintenance of irrigation networks, the areas that run the rice fields from upstream to downstream, so that the benefits of irrigation can be felt maximally. Hence, P3A is required for maximum management and maintenance by using participatory management approach. Basically, participatory irrigation management and maintenance approach is a strategic approach in managing irrigation infrastructure through farmer participation in all aspects of irrigation management, including planning, design, implementation, development (development/rehabilitation), and financing.